2011
DOI: 10.1111/j.1467-2979.2011.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Theories and behavioural drivers underlying fleet dynamics models

Abstract: International audienceIn the domain of decision-support tools for the management of marine fish resources, considerable attention has been paid to the development of models explaining how fish stocks change over space and time. In most models, fishing effort is assumed to be exogenous and determined by factors such as management. Increasingly, there has been a call for bio-economic models to also account for the dynamics of fishing fleets, recognizing that fishers respond to changing environmental, institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(142 citation statements)
references
References 138 publications
(259 reference statements)
2
135
0
5
Order By: Relevance
“…Theoretical studies suggest over-quota discarding and high-grading occur under specific conditions (Anderson 1994;Turner 1997;Parslow 2010;van Putten et al 2012). However, empirical evidence for high-grading is scarce, although there is anecdotal information from the fishing industry.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies suggest over-quota discarding and high-grading occur under specific conditions (Anderson 1994;Turner 1997;Parslow 2010;van Putten et al 2012). However, empirical evidence for high-grading is scarce, although there is anecdotal information from the fishing industry.…”
Section: Introductionmentioning
confidence: 99%
“…However, the behaviour of fishermen cannot be explained exclusively on the basis of solving an economic problem of income maximisation, since there are numerous key drivers that need to be incorporated into empirical models if the dynamics of the fleets and the behaviour of fishermen themselves are to be understood (Putten et al, 2011). For example, Hannesson (1998) stresses that institutional factors, such as the rigidity of the system for allocating TACs, lead in themselves to a race to catch stocks.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, little information available on capacity dynamics through changes of owners, including on the spatial extent of capacity redistribution (Fulton et al 2011;van Putten et al 2011b). A previous description showed that 40-50 % of traded vessels change maritime fishing districts and 25-40 % change regions through the operation of the second-hand market in the French Atlantic Ocean .…”
Section: Introductionmentioning
confidence: 99%